Socio-educational approach and oral communicative competence in secondary education - Arnao Vásquez, Marco (2014)
The present research was conducted in order to develop in students the Oral Communicative Competence from the cognitive, communicative and sociocultural approach as a teaching model. The pedagogical model was inspired by the principles of the approach under socioformativo methodology socioformativos projects. From an interdisciplinary perspective resorted to theoretical systematization of the principles of text linguistics and discourse analysis to define and delimit the scope of the nature of oral discourse genre. The strategy of the investigation was focused on qualitative research in form of action research. This made each of its stages is implemented as an objective to achieve: diagnosis, planning, implementation and evaluation. It is concluded that the socioformativo project “Communicating from our cultural reality “had positive results.